Disseminated BCG in an infant with interleukin-12 receptor B1 (IL12RB1) deficiency. (February 2015) - Senanayake, Manouri P.; Kumararatne, D. S.; Doffinger, Rainer; Barcenas-Morales, Gabriela
Abstract : Although neonatal vaccination with bacille Calmette–Guérin (BCG) is considered to be safe, complications with disseminated disease are associated with underlying immuno-deficiency disorders. A BCG-vaccinated 4-month-old girl of Sri Lankan parentage developed progressive left axillary lymphadenopathy and severe bronchopneumonia. Lymph node biopsy demonstrated epithelioid granulomata and acid-fast bacilli. An older sibling had had a similar clinical presentation and the outcome had been fatal. Investigation for immuno-deficiency detected complete IL12RB1 deficiency. Full recovery followed a prolonged course of anti-tuberculous chemotherapy. She was put on lifelong isoniazid prophylaxis. In HIV-negative infants with unusual complications related to BCG vaccination, a primary immuno-deficiency disorder should be considered.